Differential effects of high dose omega-3 fatty acids on metabolism and inflammation in patients with obesity: eicosapentaenoic and docosahexaenoic acid supplementation - Borja-Magno, Angélica; Guevara-Cruz, Martha; Flores-López, Adriana; Carrillo-Domínguez, Silvia; Granados, Julio; Arias, Clorinda; Perry, Mary; Sears, Barry; Bourges, Hector; Gómez, F. Enrique (Frontiers in Nutrition, 2023)
Background Obesity is complicated by low-grade chronic inflammation characterised by increases in inflammatory proteins and cells in peripheral blood. It has been known that omega-3 fatty acids (FA) like eicosapentaenoic (EPA) and docosahexaenoic (DHA) could modulate the inflammatory process and improve metabolic markers. Objective This study aimed to determine the effect of high-dose omega-3 FA on metabolic and inflammatory markers among patients with obesity and healthy volunteers. Methods This prospective study included 12 women with obesity (body mass index [BMI] ≥ 35.0 kg/m2) and 12 healthy women (BMI < 24.0 kg/m2) who were supplemented with a dose of 4.8 g/day (3.2 g EPA plus 1.6 g DHA) for 3 months followed by no treatment for 1 month. Plasma metabolic and inflammatory markers and levels of mRNA transcripts of CD4+ T lymphocyte subsets were determined monthly. Results None of the participants exhibited changes in weight or body composition after study completion. EPA and DHA supplementation improved metabolic (insulin, Homeostatic Model Assessment of Insulin Resistance [HOMA-IR], triglyceride [TG]/ high-density lipoprotein [HDL] ratio, TG, and arachidonic acid [AA]/EPA ratio) and tumor necrosis factor-alpha (TNF-α). Moreover, the levels of mRNA transcripts of T CD4+ lymphocyte subsets (TBX21, IFNG, GATA-3, interleukin [IL]-4, FOXP3, IL-10 IL-6, and TNF-α), were down-regulated during the intervention phase. After 1 month without supplementation, only insulin, HOMA-IR and the mRNA transcripts remained low, whereas all other markers returned to their levels before supplementation. Conclusion Supplementation with high-dose omega-3 FAs could modulate metabolism and inflammation in patients with obesity without weight loss or changes in body composition. However, these modulatory effects were ephemeral and with clear differential effects: short-duration on metabolism and long-lasting on inflammation.